9(c-5)+4=3+c-44

Simple and best practice solution for 9(c-5)+4=3+c-44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(c-5)+4=3+c-44 equation:


Simplifying
9(c + -5) + 4 = 3 + c + -44

Reorder the terms:
9(-5 + c) + 4 = 3 + c + -44
(-5 * 9 + c * 9) + 4 = 3 + c + -44
(-45 + 9c) + 4 = 3 + c + -44

Reorder the terms:
-45 + 4 + 9c = 3 + c + -44

Combine like terms: -45 + 4 = -41
-41 + 9c = 3 + c + -44

Reorder the terms:
-41 + 9c = 3 + -44 + c

Combine like terms: 3 + -44 = -41
-41 + 9c = -41 + c

Add '41' to each side of the equation.
-41 + 41 + 9c = -41 + 41 + c

Combine like terms: -41 + 41 = 0
0 + 9c = -41 + 41 + c
9c = -41 + 41 + c

Combine like terms: -41 + 41 = 0
9c = 0 + c
9c = c

Solving
9c = c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
9c + -1c = c + -1c

Combine like terms: 9c + -1c = 8c
8c = c + -1c

Combine like terms: c + -1c = 0
8c = 0

Divide each side by '8'.
c = 0

Simplifying
c = 0

See similar equations:

| x=20+4x | | 28=-20+8x | | 9x+5=96 | | 10+q-3=30 | | 9x+23=131 | | -4-6x=-3x-22 | | 2r+6=-21 | | -4x+7=13 | | 6-4x=18+2x | | 4x^7-12x^4+48x^2-64=0 | | 2(6)+3(5+3)=21 | | 2(x+1)+4=18 | | xy^2= | | 5n+20=-60 | | -90=42-11x | | 4(w)-18=-34 | | f(4)=45000(1+0.0115/4)1(4) | | .5(x+8)=10 | | -46-8x=-190 | | 5(4x+1)=2x-6x | | 73-3=18 | | 2(x+1)+4x=38 | | x=16x-x^2 | | K-y=k+wx | | M+16=200 | | 182=x+2x+(x+18) | | 2(12)+3(12+3)= | | -24+9x=-78 | | 20+n=0 | | 5x+6=6-(7x-5) | | (x)(x+1)=25 | | 13+2x=45 |

Equations solver categories